1971
DOI: 10.1126/science.172.3988.1128
|View full text |Cite
|
Sign up to set email alerts
|

Runoff of Deicing Salt: Effect on Irondequoit Bay, Rochester, New York

Abstract: Salt used for deicing the streets near Rochester, New York, has increased the chloride concentration in Irondequoit Bay at least fivefold during the past two decades. During the winter of 1969-70 the quantity and salinity of the dense runoff that accumulated on the bottom of the bay was sufficient to prevent complete vertical mixing of the bay during the spring. Comparison with 1939 conditions indicates that the period of summer stratification has been prolonged a month by the density gradient imposed by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 2 publications
2
25
0
1
Order By: Relevance
“…For municipal wastewater during cold winter periods also salt peaks from di-icing road salts might influence the settling rate. The concentrations of salts in runoff water can be up to 4 g chloride per litre (Bubeck et al, 1971) and can lead in extreme cases to floatation and washout of the sludge since the diffusion of salt into the granule can take up to 30 min ( Fig. 4A and B).…”
Section: Discussionmentioning
confidence: 98%
“…For municipal wastewater during cold winter periods also salt peaks from di-icing road salts might influence the settling rate. The concentrations of salts in runoff water can be up to 4 g chloride per litre (Bubeck et al, 1971) and can lead in extreme cases to floatation and washout of the sludge since the diffusion of salt into the granule can take up to 30 min ( Fig. 4A and B).…”
Section: Discussionmentioning
confidence: 98%
“…The salts are easily washed downstream, buE upon enLering lakes or bays, their effects can be much longer lasting. Bubeck, et al (1971), and Diment, et al (1973), exarnined the effects of de-icing salt runoff on a bay in Rochester, New York, and found that the chloride concentratioo had increased five-fold during Ehe previous 20 years. A buildup of dense saline layers in the bay prevented complete verEical nixing in the spring and, as a result, the lower layers of water were wichout oxygen for nany monEhs.…”
mentioning
confidence: 94%
“…During the past decade, a number of studies have been conducted on the effects of these loadings upon aquatic habitats (Judd, 1970;Bubeck et al, 1971;Dickman & Gochnauer, 1978;Hoffman et al, 1981).…”
Section: Introductionmentioning
confidence: 99%